Evaluation of occlusal status of Japanese adults based on functional tooth units - Takashi Zaitsu; Mari Ohnuki; Yuichi Ando; Yoko Kawaguchi (Elsevier, 2022)
Objectives: Although extensive national oral health data on dental caries and periodontal diseases in Japan are available, few studies have assessed the occlusal status of the Japanese population, and none are based on national survey data. The presence and prosthodontic conditions of the molar region are important for masticatory function, and the functional tooth unit (FTU) approach can be used to evaluate the occlusal status. Thus, using the national oral health survey data, this study investigated the occlusal status of the Japanese population using FTU. Methods: Overall, 3,605 adults (aged ≥20 years) who participated in the 2011 Japanese national oral health survey were included. FTUs were used as indices for evaluating the occlusal status. FTUs were calculated according to sex, age group, and the number of teeth present, and their associations were further analysed. Results: The number of teeth present, posterior teeth, and FTUs decreased with age in both men and women. In the age group of those ≥60 years, all only natural teeth-FTU (n-FTU) and natural teeth and artificial teeth from fixed prostheses or implant-supported FTU (nif-FTU) scores were <8. The total-FTU scores of all age groups, except the 60-69 and 70-79 years age groups, were >10. Conclusion: This is the first study to use FTUs and national oral health survey data to investigate the occlusal status in the Japanese population. People aged ≥60 years who have low n-FTU or natural teeth and artificial teeth from fixed prostheses or implant-supported FTU scores or those aged 60-70 years who have the lowest total-FTU scores require careful evaluation of masticatory performance.